Aplikasi Penjadwalan Lonceng Elektronis Berbasis Kendali Komputer - Jatmiko, Yuni; Prabowo, Nugroho Agung (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
ABSTRACT Technological Growth of electronics in the field of interface very fast and start to extend extendedly it him microprocessor or even computer personal. Implementation from interface very immeasurable in various area, start from industry till to household. Bell go to school to represent the very simple communications equipments is which is there are in school - go to school the. Bell go to school this there is assorted. Than traditional till being based on elektronis. Therefore, in this report is implementation writer will a bell application go to school the elektronis being based on computer expected by good for the schools. Application designed represent the applying of control system and scheduling of bell elektronis being based on computer of where all system is system automasi. Target of this application making so that watering down pengoperasi bell needn't be instantaneous operate the bell. Other target is so that environment go to school more recognizing of world of computer and interface This research will elaborate about software and hardware yielded at each development phase. While its implementation is limited by only at one of the module process to in each existing system, and final phase of software development and done/conducted by hardware of evaluation to process and software development and hardware hence yielded by a System made can be used direct at condition of reality.